PEMANFAATAN ABU PECAHAN LIMBAH GENTENG SEBAGAI SUBSITUSI FLY ASH PADA PEMBUATAN MORTAR GEOPOLIMER - Rakananto S, M Rendy; Firdaus, Firdaus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Mortar or mortar is a mixture of cement paste (bonding material), sand, and water. In this study, mortar will use additional tile ash as a substitute for fly ash. The tile ash to be investigated as a partial substitute for fly ash is the ash that passes sieve no.200 The percentage of mortar mixture consists of 4 variations, namely tile ash content of 0%, 5%, 10%, and 15%, and testing was carried out at 7 days, 14 days, and 28 days. Based on the research results, it was found that the addition of tile ash with a certain percentage can affect the compressive strength of mortar. The highest compressive strength of mortar occurred when 5% tile ash was added, namely 11.86 MPa for mortar aged 7 days, 13.66 MPa at design age 14 days, and 16.46 MPa at 28 days old. Meanwhile, the lowest compressive strength occurred when 15% tile ash was added, namely 11.53 MPa at 7 days, 12.46 MPa at 14 days at a percentage of 10%, and 15.06 MPa at 28 days.Keywords: roof tiles, fly ash, mortar,Fly Ash,Compressive strength